RECONSTRUCTION OF LEGAL DISPUTES MEDIATION IN HEALTH CARE FOR PATIENTS HOSPITAL BASED ON THE VALUE OF JUSTICE - Teguh Anindito; Gunarto Gunarto; Jawade Hafidz (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Mediation dispute resolution health was originally an alternative dispute resolution, when the mechanism of litigation is deemed unsatisfactory. Dissertation with the title of the reconstruction of legal mediation in disputes over health care for hospital patients based on values of justice     This study aims to discover the reality of the use of mediation in disputes over health care for hospital patients today, analyzing the ratio of mediation in disputes over health services and dispute mediation reconstruct health services for hospital patients based on values of justice.        Research carried out by empirical juridical approach, related to the implementation of health care dispute mediation. Samples were taken by purposive non-random sampling. Informant is all parties involved in the dispute resolution mediation health services, which consist of the patient's family, lawyers, hospitals / doctors, police officers and notaries. Results were analyzed and described by descriptive qualitative.        Research shows that the reality of the implementation of the health mediation has not been carried out in accordance with Article 29 of Act 36 of 2009 on Health ordered mediation in the event of a dispute of medical services and the Supreme Court Regulation No. 1 Year 2016 on Procedures for Mediation in the Court. The findings of the study found that the existing mediation done by involving the police, lawyer or notary. After comparing the model of mediation conducted in Japan, Malaysia and Singapore it is obtained a construction dispute mediation, health services based on values of justice, namely: a. Reconstruction of value by way of consensus. Seek mediation rather than litigation. Mediation aims to achieve a win-win solution for the provision of compensation to patients. b. Reconstruction of the legal form of Amendment Act No. 29 of 2004 on the Practice of  Medicine, especially with the addition of sub-section on Article 64 and Article 72. Triangular Theory of mediation Mediation is required to produce that meets the expectations of all parties. Mediation is not just an alternative dispute resolution, but mediation is imperative for the parties to the dispute in the health service. Recommendation that the settlement through mediation is imperative as well as the need for a mediation agency especially healthKeywords: Mediation, Dispute Health Services, Justice Values